2019
DOI: 10.1016/j.jaci.2018.03.023
|View full text |Cite
|
Sign up to set email alerts
|

Induction of bystander tolerance and immune deviation after Fel d 1 peptide immunotherapy

Abstract: These observations suggest that immune tolerance induced by peptide immunotherapy can be used experimentally to treat an allergic response to another allergen and that the molecular mechanisms underlying induction of tolerance to a treatment-specific allergen and a bystander allergen might be different.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 59 publications
2
20
0
1
Order By: Relevance
“…Many trials with T‐cell peptides have shown limited efficacy and/or led to nonimmediate allergic reactions during treatment although immunologic effects were demonstrated …”
Section: Current Managementmentioning
confidence: 99%
“…Many trials with T‐cell peptides have shown limited efficacy and/or led to nonimmediate allergic reactions during treatment although immunologic effects were demonstrated …”
Section: Current Managementmentioning
confidence: 99%
“…Consequently, the design of molecular AIT is based on the selection of clinically relevant allergens from any allergenic source. We cannot also exclude that AIT based on single molecules could trigger the activation of bystander Tregs, conferring protection against other allergens, as previously shown …”
Section: Discussionmentioning
confidence: 88%
“…1,2 Peptides may have a short half-life after administration and need to be phagocytosed by DCs for presentation to T cells to exert their tolerogenic activity. Nonetheless, AIT requires large amounts of allergens that need to be administered over prolonged periods of time and treatment can induce severe side effects.…”
Section: Subcutaneous Immunotherapy Using Modified Phl P5a-derived Pementioning
confidence: 99%
“…Unfortunately, treatment response to peptide AIT is suboptimal for most allergens. 1,2 Peptides may have a short half-life after administration and need to be phagocytosed by DCs for presentation to T cells to exert their tolerogenic activity. We have previously designed a novel strategy to increase uptake and presentation of peptides by DCs, while also influencing their tolerogenic phenotype.…”
Section: Subcutaneous Immunotherapy Using Modified Phl P5a-derived Pementioning
confidence: 99%
See 1 more Smart Citation